Dietary intake of adults with and without diabetes: results from NHANES 2013–2016. Issue 1 (23rd October 2020) - McClure, Scott T; Schlechter, Haley; Oh, Susan; White, Karen; Wu, Beiwen; Pilla, Scott Jordan; Maruthur, Nisa M; Yeh, Hsin-Chieh; Miller, Edgar R; Appel, Lawrence J
Abstract : Introduction: Diet is a critical aspect of the management of adults with diabetes. This paper aims to compare dietary intakes of key macronutrients and micronutrients of US adults with and without diabetes and across the spectrum of diabetes. Research design and methods: We compared absolute and energy-adjusted dietary intake of major macronutrients and micronutrients among those with and without diabetes and across the spectrum of glycemic control using a 24-hour dietary recall from a cross-sectional, nationally representative sample of 9939 US adults, 20+ years old (National Health and Nutrition Examination Survey 2013–2016). Diabetes was defined as an glycohemoglobin A1c (HbA1c)≥6.5%, fasting glucose ≥126 mg/dL, serum glucose at 2 hours following a 75 g glucose load (oral glucose tolerance test) ≥200 mg/dL, any diagnosis of diabetes or use of diabetes medication (self-reported). Results: Percent of calories from macronutrients was similar for those with and without diabetes (p>0.05, energy adjusted and adjusted for age, race, and sex). In both groups, sugar accounted for about 20% of calories. Those with diabetes consumed about 7% more calcium (p=0.033), about 5% more sodium (p=0.026), and had lower diet quality (Healthy Eating Index-2015, p=0.021) than those without diabetes. Among those with diabetes, those with an HbA1c>9.0% consumed about 4% less magnesium (p-analysis of variance=0.007) than those with an HbA1c<6.5%. Results were similar within strata of age, race, and sex. Macronutrient intake did not vary consistently by HbA1c level. Conclusions: In this nationally representative sample, there were no substantial or consistent differences in the dietary intake of macronutrients or micronutrients between US adults with and without diabetes. Improving the diets of those with diabetes will likely require enhanced targeted efforts to improve the dietary intake of persons with diabetes, as well as broad efforts to improve the dietary intake of the general population.